The world's longest known parallel temperature dataset: A comparison between daily Glaisher and Stevenson screen temperature data at Adelaide, Australia, 1887–1947. (4th October 2021) - Ashcroft, Linden; Trewin, Blair; Benoy, Mac; Ray, Darren; Courtney, Catherine
Abstract: Weather observing stations are subject to changes in instrumentation, location and surrounding environment over time. Parallel observations between old and new conditions are therefore vital to ensure that a reliable dataset can be built and used for long‐term climate analysis. Here, we examine the world's longest known sets of parallel temperature observations: daily data for Adelaide, South Australia, recorded using two different thermometer screens for 60 years from 1887 to 1947. These data are globally significant for their length and completeness, but the daily observations in the Glaisher stand have only recently been digitized for analysis. We find maximum temperatures recorded in the Glaisher stand are warmer than the Stevenson screen observations, with the difference increasing with absolute temperature, while minimum temperatures recorded in the Glaisher stand are consistently slightly cooler. These differences are similar to those identified using monthly means, as well as other studies of shorter datasets. However, the daily resolution enabled us to identify periods of inconsistent relationships due to changes in observations times (particularly from 1938 onwards), and quantify the differences during extreme events. In particular, percentile analysis revealed that the differences for extremely high temperatures are only slightly greater than the average difference during the warmer months. The data provide an opportunity to attempt the development of 160‐year continuous daily temperature record for one of the oldest colonial cities in the Southern Hemisphere. As expected, we find temperatures in recent decades to be the highest since 1859, although the Glaisher stand maximum temperature data in the 1860s are notably warm, likely due to dry conditions and persistent inhomogeneities. While the relationships we have identified cannot be applied to other 19th century Glaisher stand observations without careful metadata examination, they provide a possible tool for analysis and re‐examination of historical mid‐latitude temperature observations elsewhere around the world. Abstract : We examine the world's longest known set of parallel temperature observations: daily temperature data for Adelaide, South Australia, recorded using two different thermometer screens for the 60 years from 1887 to 1947. The data then contribute to a 160‐year continuous temperature record, one of the longest in the Southern Hemisphere.